Deformation Of Lava Tounge at Semeru Volcano using Sentinel-1 DInSAR - Chandra, Yuliana Iik Iswanti; Maryanto, Sukir; Susilo, Adi; Faridha Aprilia; Mayang Bunga Puspita (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Indonesia is vulnerable to various natural disasters, especially volcanic eruptions.  Mount Semeru, located between Malang and Lumajang, is an active volcano with a history of significant eruptions.  The eruption on December 4, 2021, caused many casualties and infrastructure damage.  This research utilizes Sentinel-1 (SLC) satellite imagery to analyze deformation changes caused by the eruption, with a particular focus on DInSAR analysis to depict changes in the crater's shape.  Before the eruption, no significant volcanic activity was detected, resulting in no clear deformation changes, with a deflation range between -0.096 cm and -0.145 cm.  However, during the eruption, the outflow of lava forming lava tongues led to the formation of lava deposits that affected surface deformation.  During the eruption phase, the deformation changes indicate an inflation phase, with values ranging from 0.064 cm to 0.094 cm, reflecting surface movement due to the accumulation of volcanic material.  After the eruption, the deformation changes became more pronounced due to the perfectly and stably formed lava deposits, with an inflation value range between 0.037 cm and 0.079 cm, resulting in significant surface shifts.  Phase reading disturbances were also detected at several locations due to lahar flows that occurred during and after the eruption.  The results of this study provide beneficial information for the relevant parties in formulating disaster mitigation strategies related to Mount Semeru's activities, as well as in understanding the dynamics of surface deformation influenced by eruptions, lava flows, and the formation of lava tongues.